2007
DOI: 10.1088/0963-0252/16/3/016
|View full text |Cite
|
Sign up to set email alerts
|

Validating experimental and theoretical Langmuir probe analyses

Abstract: Analysis of Langmuir probe characteristics contains a paradox in that it is unknown a priori which theory is applicable before it is applied. Often theories are assumed to be correct when certain criteria are met although they may not validate the approach used. We have analysed the Langmuir probe data from cylindrical double and single probes acquired from a dc discharge plasma over a wide variety of conditions. This discharge contains a dual-temperature distribution and hence fitting a theoretically generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Ion density: The Orbital Motion Limited theory (OML) is used to interpret ion current and ion density. For OML theory to be valid, the sheath surrounding the probe should be collision-less, which is generally valid for the condition ξ = (r p /λ De ) < 1 [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion density: The Orbital Motion Limited theory (OML) is used to interpret ion current and ion density. For OML theory to be valid, the sheath surrounding the probe should be collision-less, which is generally valid for the condition ξ = (r p /λ De ) < 1 [66].…”
Section: Discussionmentioning
confidence: 99%
“…Using an appropriate model for charged particle collection in collisionless conditions, the ion and electron density can be determined directly from the saturation regions of the I-V characteristic without the knowledge of electron temperature. To be able to assume collision-less sheath conditions and therefore a simple probe analysis, the probe radius and the Debye screening length, λ De = ( 0 T e /en e ) 1/2 , should be less than both the electron-neutral λ en and ion-neutral λ in mean-free-paths [66,67]. In HiPIMS discharges, with plasma densities varying typically between 10 9 to 10 12 cm −3 , one calculates that λ De ∼ 0.010 -0.19 mm, λ en ∼ 20 -117 mm, λ in ∼ 9 -27 mm for electron energies typically between 5 and 100 eV and therefore the conditions…”
Section: Probe Designmentioning
confidence: 99%
“…From the application of the semi log plot method to the Langmuir probe data taken in the source sec tion, the dual electron temperatures are obtained after the removal of ion current component [11]. This is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…When the values of the plasma parameters deduced from these theories are compared to the values of the plasma parameters obtained using the much higher electron current in the electron saturation zone, depending on the plasma conditions, it is found that either the radial or the orbital theories are consistent with the well-established electron saturation zone theory. This implies a paradox when the ion current is used in plasma diagnosis, given that the appropriate theory that should be used is not known a priori before it is used in plasma diagnosis [1,4,25]. Actually, in many situations which depend on the plasma discharge power and the pressure, values for the ion current collected by the probe between the two theories are measured in experiments [5,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…25 [1,2,4,26,28], which accounts for V p values in the rangeV p (V) ∈ [2.15, 9.48]for the given range of electron temperatures T e (K) ∈ [1000, 4400]. A single point in the Sonin plot is obtained for each set of plasma conditions-that is, for each set of experimental values for I + V p , n…”
mentioning
confidence: 99%